Acceptability and feasibility of 400 μg buccal misoprostol after 200 mg mifepristone for early medical abortion in Georgia. (2nd September 2016) - Tsereteli, Tamar; Chong, Erica; Louie, Karmen; Bokhua, Zaza; Winikoff, Beverly
Abstract: Objectives: The aim of the study was to examine the acceptability and feasibility of early medical abortion using 200 mg mifepristone and 400 μg buccal misoprostol in Georgia, outside the capital city of Tbilisi. Methods: A total of 622 women in four regions of western and eastern Georgia who presented for termination of pregnancy at up to 63 d of gestation were enrolled in the study. In the western regions, women took one 200 mg pill of mifepristone in the clinic and were given the option of administering 400 μg misoprostol buccally, either at the clinic or at home, 24–48 h later. In the eastern region, women were given the option to take both drugs at home. Abortion status was determined 2 weeks after mifepristone administration. Results: Ninety-five percent of participants had a successful abortion. Twenty-one percent of women in the eastern region elected to take mifepristone at home; nearly all participants in both regions (98%) chose to take misoprostol at home. Ninety-five percent of women were very satisfied or satisfied with the method, and 95% said they would prefer medical abortion for a future procedure. Conclusions: Medical abortion with mifepristone and 400 μg buccal misoprostol is an acceptable and feasible option for women in Georgia, outside the capital city of Tbilisi.